STUDI HUKUM ISLAM TENTANG PERAN BABYSITTER DALAM MENGGANTIKAN KEWAJIBAN HADHANAH TERHADAP ANAKNYA DI “TPA MEDIA CINTA ILMU” KELURAHAN TLOGOANYAR KECAMATAN LAMONGAN KABUPATEN LAMONGAN - Inti Haul Khusna; Nur Hasan; Dwi Ari Kurniawati (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2019)
Islam teaches the obligatory care of parents for their children for the continuity of their children's future, but lately there have been few parents who carry out their obligations due to economic factors, so they leave their children in TPA under the supervision of a babysitter who replaces their parents' duties. The purpose of this study is to describe the way babysitters take care of children in